Analysis of silicones released from household items and baby articles by direct analysis in real time-mass spectrometry - Gross, Jürgen H. (Journal of the American Society for Mass Spectrometry, 2015)
Direct analysis in real time-mass spectrometry (DART-MS) enables screening of articles of daily use made of polydimethylsiloxanes (PDMS), commonly known as silicone rubber, to assess their tendency to release low molecular weight silicone oligomers. DART-MS analyses were performed on a Fourier transform ion cyclotron resonance (FT-ICR) mass spectrometer. Flexible silicone baking molds, a watch band, and a dough scraper, as baby articles different brands of pacifiers, nipples, and a teething ring have been examined. While somewhat arbitrarily chosen, the set can be regarded as representative of household items, baby articles, and other objects made of silicone rubber. For comparison, two brands of silicone septa and as blanks a glass slide and a latex pacifier were included. Differences between the objects were mainly observed in terms of molecular weight distribution and occasional release of other compounds in addition to PDMS. Other than that, all objects made of silicone rubber released significant amounts of PDMS during DART analysis. To provide a coarse quantification, a calibration based on silicone oil was established, which delivered PDMS losses from 20 μg to >100 μg during the 16-s period per measurement. Also, the extraction of baking molds in rapeseed oil demonstrated a PDMS release at the level of 1 μg mg(-1). These findings indicate a potential health hazard from frequent or long-term use of such items. This work does not intend to blame certain brands of such articles. Nonetheless, a higher level of awareness of this source of daily silicone intake is suggested.
Epub 2014 Dec 16
Gesehen am 12.08.2020